TANGGUNGJAWAB HUKUM BAGI NOTARIS TERHADAP AKTA YANG DIBUATNYA SECARA PERDATA - Sugih Ayu Pratitis; Rehulina rehulina (Ilmu Hukum Prima (IHP), 2022)
The notary is a public official who is authorized to make an authentic deed, as long the making of the authentic deed is not reserved for other public officials. A notary as a public official is a person who carries out some the public functions of the state, especially in the field civil law. Making authentic deeds is required by laws and regulations to create certainty, order, and legal protection. This study uses normative juridical approach, using primary law, especially regarding the laws and regulations concerning the Notary Position. In this study, data were collected through study of documents and literature studies. Research on secondary legal materials derived from library sources in the form of books, articles, and interviews as a compliment. The data will be analyzed descriptively qualitatively.Civil liability of a Notary who commits an unlawful act is that the Notary is obliged to account for his actions by being sentenced to civil sanctions in the form of reimbursement costs or compensation to parties who are harmed for unlawful acts committed by the Notary. However, before the Notary is sentenced to civil sanctions, the Notary must first be able to prove that there has been a loss caused by the unlawful act the Notary against the parties.